Framework for optimal energy storage duration for maximum-reliability renewable electricity - Sadhukhan, Jhuma; Sen, Sohum; Randriamahefasoa, T. M. S. (Frontiers in Energy Research, 2024)
Energy system optimization is needed for optimal sustainable net-zero electricity (NZE) mix even at regional/local scales because of the energy storage needs for addressing the intermittency of renewable energy supply. This study presents a novel regional/local energy planning model for optimum sustainable NZE mix under spatiotemporal climate/meteorological and electrical load demand constraints. A generic robust non-linear constrained mathematical programming (NLP) algorithm has been developed for energy system optimization; it minimizes the levelized cost and greenhouse gas emissions while maximizing reliability against stored energy discharge analysis (RADA). Reliability, defined as the ratio of excess stored renewable power discharge to unmet load demand, is a measure of the extent of unmet load demand met by the excess stored renewable power. Coupled with the NLP, the RADA and energy storage evaluations are used to determine the seasonal energy storage (SES) conditions and realistic renewable proportions for NZE. The significance of the proposed framework lies in determining the maximum hours of viable electrical energy storage beyond which the reliability enhancement is infinitesimal. The significant observations of this work include 96 h of maximum viable electrical energy storage beyond which the reliability enhancement is infinitesimal. While this observation is robust based on previous reports for the case of the United States, a realistic NZE mix for Southern United Kingdom is obtained as follows. Direct wind and solar sources can meet 63%, 62%, and 55% of the electricity demands in the southwest, Greater London, and southeast regions of the United Kingdom, respectively; further, battery energy storage systems can increase the renewable proportions by 21%, 22%, and 13% in these three regions. The unmet demands can be met by renewable electricity through SES. Compressed air energy storage (CAES) and pumped hydro storage offer viable SES. Following these, natural gas with carbon capture and storage (CCS), bioenergy, and hydrogen SES are the choices based on increasing cost per lifecycle climate impact potential to meet the electricity demands.